2019
DOI: 10.1002/tea.21542
|View full text |Cite
|
Sign up to set email alerts
|

Students' self‐efficacy for science in different school systems

Abstract: The important role of self-efficacy (SE) in students' motivation, engagement, persistence, and academic achievements has been reconfirmed by ample research, both in general and for STEM disciplines. As most studies focused on traditional school systems, additional research is needed on how science SE develops in different educational environments, which was the goal of this study. Data were collected from 1979 students in Grades 5-9 from 19 traditional, Waldorf, and democratic schools in Israel. Students compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 65 publications
4
36
0
1
Order By: Relevance
“…To date, science self-efficacy research has been mostly organized within disciplinary "pockets," in which researchers create and apply domain/field-specific assessment tools in examining self-efficacy within tightly defined disciplinary knowledge and skill sets (e.g., Chemers et al, 2011;Dalgety & Coll, 2006;Hiller & Kitsantas, 2016;Kardash, 2000). Findings from these studies parallel the broader academic self-efficacy literature, confirming the relationship between students' science-specific efficacy beliefs and their success in grade school and college-level science courses and programs (Britner & Pajares, 2006;Chemers et al, 2011;Dorfman & Fortus, 2019;Fencl & Scheel, 2005;Trujillo & Tanner, 2014;Villafañe et al, 2014;Zusho, Pintrich, & Coppola, 2003). This literature also speaks to the potential sources of science efficacy and the related instructional practices (Crippen & Earl, 2007;Gwilliam & Betz, 2001;Kardash, 2000;Kurbanoglu & Akim, 2010;Lent, Lopez, Brown, & Gore, 1996;Robnett et al, 2015;Usher & Pajares, 2008;Usher, Ford, Li, & Weidner, 2019) that might scaffold success, particularly for students from groups who are under-represented in STEM fields (Ainscough et al, 2016;Ballen et al, 2017;Chemers et al, 2011;Lindstrøm & Sharma, 2011;Talsma, Schüz, & Norris, 2019;Villafañe et al, 2014).…”
Section: Self-efficacy In Science Educationmentioning
confidence: 68%
“…To date, science self-efficacy research has been mostly organized within disciplinary "pockets," in which researchers create and apply domain/field-specific assessment tools in examining self-efficacy within tightly defined disciplinary knowledge and skill sets (e.g., Chemers et al, 2011;Dalgety & Coll, 2006;Hiller & Kitsantas, 2016;Kardash, 2000). Findings from these studies parallel the broader academic self-efficacy literature, confirming the relationship between students' science-specific efficacy beliefs and their success in grade school and college-level science courses and programs (Britner & Pajares, 2006;Chemers et al, 2011;Dorfman & Fortus, 2019;Fencl & Scheel, 2005;Trujillo & Tanner, 2014;Villafañe et al, 2014;Zusho, Pintrich, & Coppola, 2003). This literature also speaks to the potential sources of science efficacy and the related instructional practices (Crippen & Earl, 2007;Gwilliam & Betz, 2001;Kardash, 2000;Kurbanoglu & Akim, 2010;Lent, Lopez, Brown, & Gore, 1996;Robnett et al, 2015;Usher & Pajares, 2008;Usher, Ford, Li, & Weidner, 2019) that might scaffold success, particularly for students from groups who are under-represented in STEM fields (Ainscough et al, 2016;Ballen et al, 2017;Chemers et al, 2011;Lindstrøm & Sharma, 2011;Talsma, Schüz, & Norris, 2019;Villafañe et al, 2014).…”
Section: Self-efficacy In Science Educationmentioning
confidence: 68%
“…From a socio-cognitive viewpoint, academic motivation is formed from both contextual factors and student cognition (Anderman & Dawson, 2011;Pintrich & Schunk, 2002). Empirical studies (e.g., Dorfman & Fortus, 2019;Józsa et al, 2017) have indicated changing patterns of science motivation across grade levels. The general findings are that students' motivation tends to drop gradually as they move through the school system.…”
Section: Difference Of Age In Science Motivationmentioning
confidence: 99%
“…Hwang et al, 2016;Robinson et al, 2019) and cross-sectional studies (e.g. Dorfman & Fortus, 2019;Józsa et al, 2017), often offer a deeper understanding of individuals' differences in science motivation, which plays an important role in personalized support in enhancing children's academic motivation in particular contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Stereotype threat, or the psychosocial anxiety individuals may experience when they are concerned they will be judged based on the negative stereotypes about a group with which they identify (Steele and Aronson, 1995), may be especially salient: perceptions of stereotype threat by underrepresented minority STEM students have been linked to increased attrition to non-STEM majors (Beasley and Fischer, 2012). Bridge programs may be useful in addressing stereotype threat, because they can provide opportunities to gain STEM-related mastery experiences (Hernandez et al, 2013), which research has shown predicts STEM self-efficacy (e.g., Honicke and Broadbent, 2016;Dorfman and Fortus, 2019). Programs that offer diverse peer mentors may also be impactful, because diversity across peer mentoring in multiple STEM fields predicts higher diversity and successful graduation rates for underrepresented minority STEM students (Fox et al, 2009).…”
Section: Stem Bridge Programsmentioning
confidence: 99%